Comparing the Effectiveness of Compassion Focused Therapy and Acceptance and Commitment Therapy on the Pain Metaphorical Perception in Patients with Musculoskeletal Pain: Comparing the Effectiveness of Compassion Focused Therapy and Acceptance and Commitment Therapy on the Pain Metaphorical Perception in Patients with Musculoskeletal Pain - Seif, Maryam; Golpour, Reza; Abdollahzadeh, Hasan (International Journal of Applied Behavioral Sciences, 2025)
Background and Aim: Pain is expressed in conceptual metaphors, because it has abstract nature. Therefore, the purpose of this study was to compare the effectiveness of compassion focused therapy and acceptance and commitment therapy on pain metaphorical perception in patients with musculoskeletal pain. Materials and Methods: The method of this study was semi-experimental with a pre-test-post-test-follow-up design with a control group. The statistical population of this research included all patients with musculoskeletal pain who were referred to physical medicine and rehabilitation clinics in Tehran from January to the end of June 2024. Based on this, 45 patients with musculoskeletal pain were selected as candidates, and available, and two experimental groups and one control group (15 people in each group) were chosen by matching randomized method. All three groups responded to the Pain Metaphorical Perception Questionnaire (2024) in the pre-test, post-test, and follow-up stages. The compassion focused therapy program was implemented in eight sessions on the first experimental group and acceptance and commitment therapy conducted in nine sessions on the second experimental group, for an hour and a half weekly. The control group received no intervention. Data were analyzed using SPSS-26. Results: The findings indicated that compassion focused therapy and acceptance and commitment therapy promote the pain metaphorical perception of patients with musculoskeletal pain (F=43.34), and the effect of both treatments continues over time (P=0.001). Conclusion: It seems; Third-wave cognitive therapies such as compassion focused therapy and acceptance and commitment therapy can alter the psychological and cognitive-verbal aspects of pain.